Pembangunan Sistem Informasi Berbasis Markerless Mobile Augmented Reality Untuk Menunjang Industri Pariwisata - Abdullah 'Azzam (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2018)
Information related to tourist attractions is needed by tourists. The information can be seen through brochures and internet that has been provided by the government, the manager of the object or by a third party. Information technology is very helpful in memeberikan information needed by tourists. Augmented Reality (AR) has many advantages that can make the information provided to users more effective and efficient. Among them is by using a markerless method that can extend the detection range of AR applications so that tourists can search information from all tourist objects just by doing the scanning process. Like just in time philosophy, AR applications can be used to get the information as needed. Both of the desired tourist attraction information and in terms of connectivity required. In this research has resulted AR application with markerless method that can detect tourist object like monument from several side. In addition AR applications are created to recognize different objects so there is no error in providing information. No internet connectivity is needed in the early detection process and can use internet connectivity when needed, such as when looking for hotel room availability information.